CLOSE BINARY SYSTEMS ON LATE EVOLUTIONARY STAGES - Cherepashchuk, A. M. (Одеські астрономічні публікації, 2017)
Observational and theoretical progress in investigations of close binary stars allow to understand the nature and evolution of many types of close binary systems containing peculiar components: Wolf-Rayet stars, white dwarfs neutron stars and black holes. Catalogue of evolved close binary systems of stars after first mass exchanges has been published by our group in 19S9. Second edition of this catalogue is now in preparation and will be published in 1995 by Gordon & Breach.